Utveckling och implementering av Charge Point Operator - Ask, Simon; Khudhair, Heba (My University, 2021)
Since its entry into the regular car market around 2010, electric car production has increased with each passing year. Today, Sweden’s passenger car fleet consists of about 4% electric vehicles. It is essential that the charging infrastructure keeps up with the development so that rechargeable vehicles can be a market that is making an impact. For this to happen, more charging stations and servers are required that can communicate in a seamlessly. In this project, a Charge Point Operator has been developed whose intention is to act as a server for a charge point. The work presented in the report aims to be used in Drifter World AB’s operations and examine the positive and negative sides of the Charge Point Operator. With the help of the communication protocol Open Charge Point Protocol, a server has been developed that communicates with the connected charge point via informational messages. During the work, a Charge Point Operator was tested against a simulated charge point to later be tested against hardware in the form of a real charge point. The simulation tests the message exchange for start-up, heartbeat, authorization and start of charge. The test showed how the exchange worked from the perspectives of the charge point and the Charge Point Operator. When testing real hardware, connectivity, heart rate, status messages, start och charging and stop of charging were tested. The test shows possible test errors as charging ended and the car used in the test disconnected from the charging session. The hardware was of the exhibition type and should be replaced with a charge point that can perform a complete charging session. It is also possible that the fault lies with the electric car due to unknown reason. Open Charge Point Protocol versions 1.6 and 2.0.1 were tested for the hardware and the simulation, respectively, and it is recommended to use one of the versions during similar tests. As Drifter World AB is developing a payment method that will facilitate the electric motorist’s charging possibilities, Charge Point Operator is a positive expansion of their business. A next step would be to test measured value messages as it is an important part for businesses active in the electric car’s ecosystem. Without measurement value messages, it becomes difficult to, for example, charge for charging or know how long charging has been going on.
Keywords: CPO; Charge Point; OCPP; simulate; testing